INFLASI, TINGKAT SUKU BUNGA, NILAI TUKAR DAN PENGARUHNYA TERHADAP PENANAMAN MODAL ASING DI INDONESIA - Zumaeroh; Miftakhul Jannah; Diah Retnowati (Majalah Imiah Manajemen & Bisnis, 2020)
Foreign and domestic investment is the first step in development activities and economic growth. Sufficient capital will bring economic growth and will improve people's welfare for entrepreneurs who need funds to develop their businesses. The analytical method used in this study is a multiple linear regression analysis method carried out with Eviews 9. One of the requirements to test multiple linear regression analysis needs to be tested on classical assumptions. This is needed so that the resulting regression equation is BLUE (Best, Linear, Unbiased, Estimator). In addition to assessing the goodness of fit of a model, the coefficient of determination, f test and t test were tested. This study uses quarterly data for the 2010-2018 period for each research variable. The results of this study show that simultaneously the variables of inflation, interest rates and exchange rates have a significant effect on FDI in Indonesia. Partially, inflation and exchange rates have a positive and significant effect on FDI in Indonesia, while interest rates have a negative effect on FDI in Indonesia